Cultural Adaptation of the Mothers and Babies Intervention for Use in Tribal Communities - Ward, Erin A.; Iron Cloud-Two Dogs, Ethleen; Gier, Emma E.; Littlefield, Linda; Tandon, S. Darius (Frontiers in Psychiatry, 2022)
Objective: While one in five women may experience mood and anxiety disorders during pregnancy and postpartum, Indigenous identity increases that risk by 62%, especially among younger Indigenous women. The need for evidence-based perinatal mental health interventions that provide culturally relevant well-being perspectives and practices is critical to improving maternal, child, and community outcomes for Indigenous peoples, and reducing health inequities. Methods: Through a collaboration between community maternal and child health professionals, intervention researchers, and a cultural consultant, our workgroup developed cultural adaptations to Mothers and Babies, an evidence-based perinatal depression prevention intervention. Applying a cultural interface model, we identified existing intervention content for surface adaptations, as well as deep, conceptual adaptations to incorporate traditional teachings throughout the intervention. Results: This collaboration developed a culturally adapted facilitator manual for intervention providers, including guidance for implementation and further adaptation to represent local tribal culture, and a culturally adapted participant workbook for Indigenous perinatal women that reflects cultural teachings and traditional practices to promote well-being for mother and baby. Implications: Committing to a culturally respectful process to adapt Mothers and Babies is likely to increase the reach of the intervention into Indigenous communities, reengage communities with cultural practice, improve health outcomes among parents, children, and the next generation’s elders, and reduce disparities among Indigenous groups. Replication of this community-engaged process can further the science and understanding of cultural adaptations to evidence-based interventions, while also further reducing health inequities. Future steps include evaluating implementation of the culturally adapted intervention among tribal home visiting organizations.